Enhanced BRET Technology for the Monitoring of Agonist-Induced and Agonist-Independent Interactions between GPCRs and β-Arrestins - Kocan, Martina; Dalrymple, Matthew; Seeber, Ruth; Feldman, Brian; Pfleger, Kevin (Frontiers in Endocrinology, 2011)
The bioluminescence resonance energy transfer (BRET) technique has become extremely valuable for the real-time monitoring of protein-protein interactions in live cells. This method is highly amenable to the detection of G protein-coupled receptor (GPCR) interactions with proteins critical for regulating their function, such as β-arrestins. Of particular interest to endocrinologists is the ability to monitor interactions involving endocrine receptors, such as orexin receptor 2 (OxR2) or vasopressin type II receptor (V2R). The BRET method utilizes heterologous co-expression of fusion proteins linking one protein of interest (GPCR) to a bioluminescent donor enzyme, a variant of Renilla luciferase, and a second protein of interest (β-arrestin) to an acceptor fluorophore. If in close proximity, energy resulting from oxidation of the coelenterazine substrate by the donor will transfer to the acceptor, which in turn fluoresces. Using novel luciferase constructs, we were able to monitor interactions not detectable using less sensitive BRET combinations in the same configuration. In particular, we were able to show receptor/β-arrestin interactions in an agonist-independent manner using Rluc8-tagged mutant receptors, in contrast to when using Rluc. Therefore, the enhanced BRET methodology has not only enabled live cell compound screening as we have recently published, it now provides a new level of sensitivity for monitoring specific transient, weak or hardly detectable protein-protein complexes, including agonist-independent GPCR/β-arrestin interactions. This has important implications for the use of BRET technologies in endocrine drug discovery programs as well as academic research.